IMPROVING STUDENTS’ PRONUNCIATION BY LISTENING TO THE AUDIO VISUAL AND ITS TRANSCRIPTION OF THE NARRATIVE TEXT - Shodiqin, Imam; Apriliaswati, Rahayu; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research aimed to improve students’ pronunciation by listening to the audio visual and its transcription of the narrative text of eight grade students of SMP S Khatulistiwa Jungkat in academic year 2013/2014. The writer applied Classroom Action Research which consisted of three cycles. The subject of this research was the second year students of class eight of SMP S Khatulistiwa Jungkat. They consist of 23 students. The data was collected using observation checklist, questionnaire, field notes, and tape recorder. Audio visual media and its transcription improved students’ pronunciation in each cycle and process of teaching and learning pronunciation. The audio visual was played several times and the students repeated by reading the transcription of the narrative text based on the audio. The transcription had been added with symbols to help the students to read the text based on the audio. The repetition of the audio and the transcription of the narrative text helped the students to improve their pronunciation. Audio visual and its transcription helped and encouraged students to learn pronunciation. In conclusion, audio visual and its transcription helped students’ improved their pronunciation. Keywords: Pronunciation, Audio Visual, Transcription Abstrak: Penelitian ini bertujuan untuk meningkatkan pengucapan siswa dengan mendengarkan audio visual dan transkripsi teks narasi siswa kelas delapan SMP S Khatulistiwa Jungkat pada tahun akademik 2013/2014. Penulis menerapkan Penelitian Tindakan Kelas yang terdiri dari tiga siklus. Subyek penelitian ini adalah siswa tahun kedua kelas delapan SMP S Khatulistiwa Jungkat. Mereka terdiri dari 23 siswa. Pengumpulan data dilakukan dengan menggunakan lembar observasi, angket, catatan lapangan, dan tape recorder. Media audio visual dan transkripsi yang meningkatkan pengucapan siswa dalam setiap siklus dan proses belajar dan mengajar pengucapan. Audio visual yang dimainkan beberapa kali dan siswa mengulanginya dengan membaca transkripsi teks naratif berdasarkan audio. Transkripsi telah ditambahkan dengan simbol untuk membantu para siswa untuk membaca teks berdasarkan audio. Pengulangan audio dan transkripsi teks naratif membantu siswa untuk meningkatkan pengucapan mereka. Audio visual dan transkripsi membantu dan mendorong siswa untuk belajar pengucapan dengan efektif. Kesimpulannya, audio visual dan transkripsi membantu meningkatkan pengucapan murid-murid. Kata kunci: Pengucapan, Audio Visual, Transkripsi